Kant, Radical Agnosticism, and Methodological Eliminativism about Things-in-Themselves - Hanna R. (Кантовский сборник, 2017)
In his recent paper, “Things in Themselves: An Interim Report,” Robert Howell says that a philosophically satisfactory resolution of all-too-familiar problems about Kant’s views on the object of knowledge and the nature of things-in-themselves should meet three conditions: (1) it should be reasonably faithful to Kant’s views, (2) it must show that his views are internally consistent and his major arguments are valid, and (3) it must not rest on premises that are themselves philosophically implausible. Howell concludes that it would be philosophically good to find a satisfactory resolution of these problems, but also suspects that no such resolution will be found. The author fully agrees with Howell’s three conditions of adequacy on a philosophically satisfactory resolution of the problems, and holds that it would be philosophically good to find a resolution of them. However, the author sharply disagrees with the statement that no such resolution can be found. Indeed, he believes that such a resolution has been found. Kantian Radical Agnosticism (KRA) says that ‘we can and do know a priori that we cannot know either the nature of things in themselves or whether things in themselves exist or do not exist’. Kantian Methodological Eliminativism (KME) about things in themselves says that for the purposes of the theory of real (i. e., anthropocentric, “humanfaced”) transcendental idealism we can completely ignore things in themselves. In this paper the author unpacks and defends both KRA and KME.